Does prior antiplatelet treatment improve functional outcome after intra-arterial treatment for acute ischemic stroke?. Issue 4 (June 2017) - Mulder, Maxim JHL; Berkhemer, Olvert A; Fransen, Puck SS; van den Berg, Lucie A; Lingsma, Hester F; den Hertog, Heleen M; Staals, Julie; Jenniskens, Sjoerd FM; van Oostenbrugge, Robert J; van Zwam, Wim H; Majoie, Charles BLM; van der Lugt, Aad; et al.
Background and purpose: In patients with acute ischemic stroke who receive antiplatelet treatment, uncertainty exists about the effect and safety of intra-arterial treatment. Our aim was to study whether intra-arterial treatment in patients with prior antiplatelet treatment is safe and whether prior antiplatelet treatment modifies treatment effect. Methods: All 500 MR CLEAN patients were included. We estimated the effect of intra-arterial treatment with ordinal logistic regression analysis, and tested for interaction of antiplatelet treatment with intra-arterial treatment on outcome. Furthermore, safety parameters and serious adverse events were analyzed. Results: The 144 patients (29%) on antiplatelet treatment were older, more often male, and had more vascular comorbidity. Intra-arterial treatment effect size after adjustments in antiplatelet treatment patients was 1.7 (95% confidence interval 0.9–3.2), and in no antiplatelet treatment patients 1.8 (95% confidence interval: 1.2–2.6). There was no statistically or clinically significant interaction between prior antiplatelet treatment and the relative effect of intra-arterial treatment ( p = 0.78). However, in patients on antiplatelet treatment, the effect of successful reperfusion on functional outcome in the intervention arm of the trial was doubled: the absolute risk difference for favorable outcome after successful reperfusion in patients on prior antiplatelet treatment was 39% versus 18% in patients not on prior antiplatelet treatment (Pinteraction = 0.025). Patients on antiplatelet treatment more frequently had a symptomatic intracranial hemorrhage (15%) compared to patients without antiplatelet treatment (4%), without differences between the control and intervention arm. Conclusions: Prior treatment with antiplatelet agents did not modify the effect of intra-arterial treatment in patients with acute ischemic stroke presenting with an intracranial large vessel occlusion. There were no safety concerns. In patients with reperfusion, antiplatelet agents may improve functional outcome.